Imitative obesity and relative utility - David G. Blanchflower; Andrew J. Oswald; Bert Van Landeghem (Institute for the Study of Labor (IZA), 2009)
If human beings care about their relative weight, a form of imitative obesity can emerge (in which people subconsciously keep up with the weight of the Joneses). Using Eurobarometer data on 29 countries, this paper provides cross-sectional evidence that overweight perceptions and dieting are influenced by a person's relative BMI, and longitudinal evidence from the German Socioeconomic Panel that well-being is influenced by relative BMI. Highly educated people see themselves as fatter - at any given actual weight - than those with low education. These results should be treated cautiously, and fixed-effects estimates are not always well-determined, but there are grounds to take seriously the possibility of socially contagious obesity.
urn:nbn:de:101:1-20090304422
Keywords: D1; I12; I31; 330; Body mass index BMI; comparisons; imitation; happiness; peer effects; dieting; mental health; well-being; obesity; Ernährungsgewohnheit; Gesundheit; Soziale Schicht; Lebenszufriedenheit; Europa